2015
DOI: 10.3109/02656736.2014.1002435
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance for clinical high intensity focused ultrasound fields

Abstract: As the use of HIFU in the clinic becomes more widespread there is an ever increasing need to standardise quality assurance protocols, an important step in facilitating the wider acceptance of HIFU as a therapeutic modality. This article reviews pertinent aspects of HIFU treatment delivery, encompassing the closely related aspects of quality assurance and calibration. Particular attention is given to the description and characterisation of relevant acoustic field parameters and the measurement of acoustic power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…The performance of phased array transducers can be evaluated using standard experimental methods commonly used for single-element transducers [114]; radiation force balance measurements can be used to quantify the total acoustic power of the array, while hydrophone measurements can provide additional information regarding the spatiotemporal pressure field generated by the device. It has been demonstrated that hydrophone measurements of a pre-focal 2D planar field can be used to infer the velocity distribution on the transducer surface as well as the pressure field in the focal region using back- and forward-projection methods, respectively [115, 116, 117, 118].…”
Section: Ultrasound Phased Arraysmentioning
confidence: 99%
“…The performance of phased array transducers can be evaluated using standard experimental methods commonly used for single-element transducers [114]; radiation force balance measurements can be used to quantify the total acoustic power of the array, while hydrophone measurements can provide additional information regarding the spatiotemporal pressure field generated by the device. It has been demonstrated that hydrophone measurements of a pre-focal 2D planar field can be used to infer the velocity distribution on the transducer surface as well as the pressure field in the focal region using back- and forward-projection methods, respectively [115, 116, 117, 118].…”
Section: Ultrasound Phased Arraysmentioning
confidence: 99%
“…Furthermore, the literature still lacks standardized reporting of US parameters, including methods of exposure and the experimental conditions. This makes it difficult to compare existing results 17,18 and means a definitive reference for our experiments is not available.…”
Section: Backing Layermentioning
confidence: 99%
“…However, the presence of permanent, high magnetic fields (1.0-3.0 T) produced by MRI systems, as well as limited bore sizes of MRI scanners pose challenges to the use of traditional techniques. 15 Hydrophone-based pressure field characterization of a clinical MR-HIFU system outside the MRI suite has been previously reported by Kreider et al 18 where the standard hydrophone method was used for the acoustic characterization of the Sonalleve V1 MR-HIFU system (Philips, Vantaa, Finland). Acoustic field measurements were made possible by special cable arrangement and by moving the HIFU patient table outside of the MRI suite, away from the magnet's fringe field.…”
Section: Introductionmentioning
confidence: 96%
“…A needle hydrophone or membrane hydrophone is normally used for lower pressure measurements and more robust sensors, such as a fiber‐optic hydrophone, are used for high‐pressure measurements. However, the presence of permanent, high magnetic fields (1.0–3.0 T) produced by MRI systems, as well as limited bore sizes of MRI scanners pose challenges to the use of traditional techniques . Hydrophone‐based pressure field characterization of a clinical MR‐HIFU system outside the MRI suite has been previously reported by Kreider et al .…”
Section: Introductionmentioning
confidence: 99%